2019
DOI: 10.4314/ahs.v19i3.34
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of hypertension in Amhara regional state city and its’ surrounding rural districts: a community-based cross-sectional study

Abstract: Background: Nowadays, among non-communicable diseases hypertension is a growing public health important disease both in developed and developing nations. Objective: The aim of this study was to determine the prevalence and associated factors of hypertension in Amhara Regional State city and its’ surrounding rural districts, Ethiopia. Method: Community-based cross-sectional study was conducted in the urban and rural communities living in Amhara Regional State city and its’ surrounding rural districts administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…In this subcategorical analysis, 15 studies were included for the assessment of residence, educational status and salt intake as risk factors for hypertension. 21,22,[26][27][28]30,32,33,[42][43][44][45]50,52 The pooled metaregression analysis showed that there is a statistically significant association between urban residence and low education status (<Grade 12) with hypertension, with the odds of 1.47 and 1.67 (95% CI: 1.28, 1.70 vs 1.38, 2.01), respectively (Figure 5). However, the pooled meta-regression analysis of salt intake showed nonsignificant association between salt intake and hypertension, with the odds of 2.70 (95% CI: 0.68, 10.73).…”
Section: Association Between Residence Educational Status and Salt Intake And Hypertensionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this subcategorical analysis, 15 studies were included for the assessment of residence, educational status and salt intake as risk factors for hypertension. 21,22,[26][27][28]30,32,33,[42][43][44][45]50,52 The pooled metaregression analysis showed that there is a statistically significant association between urban residence and low education status (<Grade 12) with hypertension, with the odds of 1.47 and 1.67 (95% CI: 1.28, 1.70 vs 1.38, 2.01), respectively (Figure 5). However, the pooled meta-regression analysis of salt intake showed nonsignificant association between salt intake and hypertension, with the odds of 2.70 (95% CI: 0.68, 10.73).…”
Section: Association Between Residence Educational Status and Salt Intake And Hypertensionmentioning
confidence: 99%
“…In this subcategorical analysis, 20 studies were included for the assessment of age as a risk factor for hypertension. 20,22,[24][25][26][27][28][30][31][32][33]37,38,[42][43][44][49][50][51][52] P Association of sex with hypertension F I G U R E Forest plot of odds ratio for the association of male sex with hypertension.…”
Section: Association Between Age and Hypertensionmentioning
confidence: 99%
See 3 more Smart Citations